The duration of Plasmodium falciparum infections. - Ashley, E; White, N (2014)
Plasmodium vivax and Plasmodium ovale are often considered the malaria parasites best adapted to long-term survival in the human host because of their latent exo-erythrocytic forms. The prevailing opinion until the middle of the last century was that the maximum duration of Plasmodium falciparum infections was less than two years. Case reports and series investigating blood donors following accidental malaria infection of blood transfusion recipients and other sporadic malaria cases in non-endemic countries have shown clearly that asymptomatic P. falciparum infections may persist for up to a decade or longer (maximum confirmed 13 years). Current policies in malaria-free countries of excluding blood donors who have lived in malarious areas are justified. Vigilance for longer than three years after declaring elimination in an area may be needed.